1997
DOI: 10.1089/dna.1997.16.1419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intestinal Phospholipase A/Lysophospholipase and Sucrase-Isomaltase Genes Suggests a Common Structure for Enterocyte-Specific Promoters

Abstract: Intestinal phospholipase A/lysophospholipase (IPAL) is an intestine-specific brush-border enzyme expressed during development and along the intestinal crypt-villus axis in a pattern similar to another well characterized brush-border enzyme, sucrase-isomaltase (SI). A tissue-specific DNase I hypersensitive site was identified in chromatin from intestinal nuclei immediately upstream from the transcriptional start site of the IPAL gene. Footprinting analysis showed that two DNA elements within the IPAL promoter w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…First, we compared the ability of overexpressed Cdx2 wild-type and 4S>A mutant to stimulate the expression of luciferase driven by Cdx2-responsive promoters. Figure 4a shows the results obtained with HCT 116 cotransfected with IPAL-Luc (Taylor et al, 1997a) and increasing doses of the plasmids encoding Cdx2 wild-type or the mutant 4S>A. As expected, wild-type Cdx2 stimulated expression of this reporter in a dose-dependent manner.…”
Section: The 4s Motif Modulates the Transcriptional Activity Of Cdx2supporting
confidence: 58%
“…First, we compared the ability of overexpressed Cdx2 wild-type and 4S>A mutant to stimulate the expression of luciferase driven by Cdx2-responsive promoters. Figure 4a shows the results obtained with HCT 116 cotransfected with IPAL-Luc (Taylor et al, 1997a) and increasing doses of the plasmids encoding Cdx2 wild-type or the mutant 4S>A. As expected, wild-type Cdx2 stimulated expression of this reporter in a dose-dependent manner.…”
Section: The 4s Motif Modulates the Transcriptional Activity Of Cdx2supporting
confidence: 58%
“…Many intestine-specific genes, such as those for sucrase-isomaltase (SI) (13,14), lactase-phlorizin hydrolase (LPH) (13,(15)(16)(17), intestine phospholipase A/lysophospholipase (18), and claudin-2 (19) have been demonstrated to be transcriptionally regulated by Cdx proteins. It has also been reported that the Cdx family is involved in intestinal carcinogenesis, differentiation, and morphogenesis using several experimental approaches (20 -23).…”
Section: Discussionmentioning
confidence: 99%
“…The intestine phospholipase A/lysophospholipase promoter also has binding sites for Cdx and HNF1 (18), although it has yet to be reported whether the HNF1 site is functional or not. The promoter regions of these genes share certain features, namely HNF1-, Cdx-, and GATAbinding sites within 200 bp upstream of their transcription initiation site (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The homeodomain proteins Cdx1 and Cdx2 are wellrecognized regulators of intestine-specific gene expression and enterocyte differentiation (Suh et al, 1994;Suh and Traber, 1996;Taylor et al, 1997;Freund et al, 1998;Soubeyran et al, 1999). Cdx1 and Cdx2 are important transcriptional activators, promoting the intestine-specific expression of a number of genes including sucrase isomaltase, colon carbonic anhydrase 1, and intestinal phospholipase A/lyso-phospholipase (IPAL) (Suh et al, 1994;Taylor et al, 1997;Drummond et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Cdx1 and Cdx2 are important transcriptional activators, promoting the intestine-specific expression of a number of genes including sucrase isomaltase, colon carbonic anhydrase 1, and intestinal phospholipase A/lyso-phospholipase (IPAL) (Suh et al, 1994;Taylor et al, 1997;Drummond et al, 1998). Cdx1 and Cdx2 also promote differentiation of intestinal cells (Suh and Traber, 1996;Soubeyran et al, 1999).…”
Section: Introductionmentioning
confidence: 99%